2011
DOI: 10.1007/s00296-011-1946-3
|View full text |Cite
|
Sign up to set email alerts
|

IL1B -511(G>A) and IL1RN (VNTR) allelic polymorphisms and susceptibility to knee osteoarthritis in Croatian population

Abstract: Osteoarthritis (OA) is a frequent, destructive joint disease, with debilitating impact on a society regarding medical, social, and economic issues. Although causes of primary OA were still not fully elucidated, evidence points to complex genetic risk that varies among different population groups, including the interleukin-1 (IL-1) gene cluster. Here, we sought to determine allelic and genotypic frequencies of the IL-1β (IL1B) and the IL-1 receptor antagonist (IL1RN) genes using single nucleotide polymorphism (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Zheng et al (2013) suggested that G rs16944 is associated with an increased risk of esophageal squamous cell carcinoma, while a meta-analysis of studies analyzing individuals of European descent Abu-Maziad et al (2010) reported that osteomyelitis of the hand was associated with rs16944. However, Jotanovic et al (2012) did not identify a significant association between this SNP and osteoarthritis in Caucasian patients. The results of our study also indicated that the frequency of the C rs3804099 allele, located in TLR2, is significantly higher in patients than in control individuals (P = 0.004, Pc = 0.04), indicating that people positive for this allele are at a twofold greater risk of H O than negative individuals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Zheng et al (2013) suggested that G rs16944 is associated with an increased risk of esophageal squamous cell carcinoma, while a meta-analysis of studies analyzing individuals of European descent Abu-Maziad et al (2010) reported that osteomyelitis of the hand was associated with rs16944. However, Jotanovic et al (2012) did not identify a significant association between this SNP and osteoarthritis in Caucasian patients. The results of our study also indicated that the frequency of the C rs3804099 allele, located in TLR2, is significantly higher in patients than in control individuals (P = 0.004, Pc = 0.04), indicating that people positive for this allele are at a twofold greater risk of H O than negative individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Table 1. Cytokine, cytokine receptor, and toll-like receptor characteristics (Lu et al, 2005;Tsezou et al, 2008;Jotanovic et al, 2012;Zheng et al, 2013)]. …”
Section: Introductionmentioning
confidence: 99%
“…Relation of the allelic variants SNP rs16944 (G/A) with impairment of AMPAR endocytosis and PTSD still obscure, at same time, there are indirectly data allowing suggest the relationship of PTSD with A-allele ("AA" genotype), SNP rs16944. It has been found that A-allele is associated with increases susceptibility to osteoarthritis [51,52], herewith patients with PTSD were more likely to have osteoarthritis [53]. Available data suggest that PTSD is highly complex and polygenic disorder.…”
Section: Introductionmentioning
confidence: 96%
“…The aim of this case-control study was to analyse IL-1 gene locus polymorphisms in Croatian knee and hip OA patients and compare them with results in other populations. We have published recently a part of this study regarding two polymorphisms in the IL-1B and IL-1RN genes [23,24]. Here, we extend it by analysing associations of four-marker extended-risk IL-1 gene locus haplotypes with hip and knee OA and focused on gender differences.…”
Section: Introductionmentioning
confidence: 99%
“…The blood was taken from OA patients during PKR, TKR or THR surgery and genomic DNA extracted as reported previously [23,24]. In detail, for the extraction of genomic DNA, 200 ll of whole blood was mixed with 400 ll of sucrose buffer (0.32 M sucrose, 10 mM Tris-HCl pH 7.5, 5 mM MgCl 2 , 1% v/v Triton X-100) and incubated for 1 min at room temperature.…”
Section: Dna Isolationmentioning
confidence: 99%